Urban riskscapes. Social and spatial dimensions of risk in urban infrastructure settings. - Neisser, Florian; Müller-Mahn, Detlef (Springer, 2018)
A central challenge of urban risk governance lies in the complexity of the overlapping of multiple risks. This problem is particularly relevant and obvious in urban infrastructure settings. The concept of riskscapes addresses and integrates various aspects of risks: the overlapping of different risks, the multiplicity of perspectives on the same spatial area and spatially different meanings and consequences. An important aspect of the riskscapes concept lies in the range of perspectives regarding the risks. This article takes a closer look at aspects of multiplicity and overlaps of different riskscapes as well as the spatial and temporal dynamics of risks and riskscapes while turning to empirical findings on the transportation of hazardous goods. This is discussed with a specific focus on stationary and mobile forms of risk in the context of urban infrastructures. Based on a comparison of risk management in the Netherlands and in Germany, an aligned risk management strategy in regard to spatial planning and hazardous incidents regulation is recommendable. A context-sensitive, practice-oriented, and socio-spatial understanding of risks is necessary to grasp the context of specific urban situations and to get an in-depth understanding of risk situations - including the aspects stationary and mobile risks.
Keywords: Umweltschutz; Stadtverkehr; Transport; Güterverkehr; Gefahrstoff; Gefahrguttransport; Unfall; Routenplanung; Stadtplanung; Raumplanung; Risikomanagement; Schutzkonzept; Internationaler Vergleich; Chemieunfall